Hubungan Perhatian Orang Tua Kristen Dengan Motivasi Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas X SMK Negeri 1 Raya Kabupaten Simalungun Tahun Pembelajaran 2023/2024. - Lisdayani Simamora; Sabar Rudi Sitompul; Limmarten Simatupang; Raikhapoor Raikhapoor; Eduward Hottua Hutabarat (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The research aims to determine the positive and significant relationship between the attention of Christian parents and the motivation to learn Christian Religious Education and Character in Class The research hypothesis is that there is a positive and significant relationship between the attention of Christian parents and the motivation to learn Christian Religious Education and Character in Class Descriptive and inferential quantitative research methods. The population of all class X students at SMK Negeri 1 Raya Simalungun Regency for the 2023/2024 academic year who are Protestant Christians is 159 people. The sample using the cluster random sampling technique is 25% of the total population, namely 25% x 159 people = 40 people. The research instrument is a closed questionnaire. The results of data analysis obtained: 1) Basic assumption test, namely: a) Normality test showed that the data for variable X and variable Y were normally distributed, b) Homoscedity test showed that the data for variable 2) The positive relationship test obtained a value of rcount=0.241<rtable=0.312, thus there is not enough evidence to say that there is a positive relationship between the attention of Christian parents and students' motivation to learn Christian Religious Education and Character. 3) Testing the hypothesis obtained tcount=1.531<ttable=2.021, so H0 is accepted and Ha is rejected. The research concluded that there is not enough evidence to say that the attention of Christian parents has a positive relationship with the learning motivation for Christian Religious Education and Characteristics of class X students at SMK Negeri 1 Raya for the 2023/2024 academic year.